Habitus Jurnalistik dan Konstruksi Kebenaran: Studi Kritis Kontradiksi Framing Berita Perang pada Republika dan Detik.Com - Muhammad Fahmi (IAINU Kebumen, 2026)
This research aims to dissect how mass media constructs the reality of war through the mechanisms of issue selection and the highlighting of specific aspects. Utilizing Robert Entman's framing model, this study explores four key elements within news texts: defining problems, diagnosing causes, making moral judgments, and providing treatment recommendations. The analytical focus is directed toward the differing framing directions between national media outlets that hold distinct ideological tendencies in portraying the actors involved in the conflict. The findings indicate that media outlets do not merely report facts on the ground; rather, they are actively engaged in the